Building real laboratories on the internet. (20th April 2005) - Forinash, Kyle; Wisman, Raymond
A majority of the pedagogical uses of computers fall somewhere within the five headings of drill, number crunching, laboratory applications, simulations, and self-paced courses (Arons, 1984). In this paper, we discuss a sixth use for computerised instruction, dispersed laboratories over the internet, one which was probably unanticipated years ago when the internet and laboratory technologies were less accessible and less friendly than now. The pervasive interconnectivity of the internet provides the means for entirely new kinds of laboratory experiences for the science student. For example, students can remotely access laboratory equipment that previously would have been too expensive or too dangerous for a typical student laboratory. Large-scale collaborative experiments between students separated geographically are also possible. This paper presents an overview of the technology for science laboratories over the internet, example laboratory experiments, and potential applications.